2013
DOI: 10.1080/00185868.2013.757953
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Assistants’ Dilemma: Caregiver Versus Caretaker

Abstract: Focus groups were conducted with over 150 certified nursing assistants (CNAs) in seven nursing homes to obtain their opinions on how the work environment supported or impeded their caregiving to residents. Strong opinions emerged about work environment interference with CNAs' ability to provide quality and comprehensive care. Participants also believed that their supervisors did not respect the value of the care and nurturing that CNAs provided. This contrasted with the respect that CNAs voiced for residents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 18 publications
(24 reference statements)
2
23
0
Order By: Relevance
“…Acts of racial discrimination along with negative comments and attitudes from staff members were specific to the racial/ethnic minority CNA experience (Berdes & Eckert, 2001;Jervis, 2002;. In turn, these weak efforts only lead CNAs to feel unsupported, stressed, and burned out (Holmberg et al, 2013). Such ignorance results in comments from supervisory staff such as 'Well, that's what you get paid to deal with' .…”
Section: Racementioning
confidence: 99%
See 3 more Smart Citations
“…Acts of racial discrimination along with negative comments and attitudes from staff members were specific to the racial/ethnic minority CNA experience (Berdes & Eckert, 2001;Jervis, 2002;. In turn, these weak efforts only lead CNAs to feel unsupported, stressed, and burned out (Holmberg et al, 2013). Such ignorance results in comments from supervisory staff such as 'Well, that's what you get paid to deal with' .…”
Section: Racementioning
confidence: 99%
“…While administrators have acknowledged being aware of these racial occurrences by residents, families, and staff members, they have either chosen not to support CNAs or simply lacked the competence to address the occurrence (Dodson & Zincavage, 2007;Foner, 1994;Holmberg et al, 2013). Moreover, staff who feel mistreated are more likely to miss work and/or not perform to their full potential at work, which in turn negatively affects resident care when turnover increases and staff burnout has the potential to culminate in resident abuse and/or neglect (Ejaz, Noelker, Menne, & Bagaka's, 2008;Holmberg et al, 2013). In turn, these weak efforts only lead CNAs to feel unsupported, stressed, and burned out (Holmberg et al, 2013).…”
Section: Racementioning
confidence: 99%
See 2 more Smart Citations
“…We conducted focus groups for needs assessment, discussed the range of possible influences on workers’ health and safety from both work and non-work sources (the integration concept central to the TWH program), and then invited them to envision and jointly brainstorm an ideal nursing home which was a health-promoting environment for the workers themselves as well as the residents for whom they provided care (Holmberg et al 2013). Qualitative evaluations showed that the team members were highly receptive to the idea of integration, the brainstorming and prioritizing of risk factors, and the participatory process for developing solutions.…”
Section: Examples Of Worker Health Dandi Researchmentioning
confidence: 99%